Enterprise iPhone and iPad Administrator$1 (Bs Guides - Edge, Charles; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Are you an IT professional involved in deploying the iPhone and or iPad in your company or organization? Do you have fellow employees who are eager to use their iPhones and iPads for work? Then this is the book for you. Enterprise iPhone and iPad Administrator$1 (Bs Guide provides step-by-step instructions on how to deploy and integrate the iPhone within a range of professional environments$1 (Bfrom large businesses and educational institutions to medium-sized offices. This book ensures that the process is achieved in a streamlined, efficient, and cost-effective manner. The guide begins with an introduction to basic deployment concerns, then moves into actual methods and tools that you can use to streamline the deployment process. Next, an in-depth discussion of configuration and provisional profiles helps you deliver solid device setup, security, and adherence to organization policies. Finally, you$1 (Bll learn how to use existing help desk teams to provide effective user support. Also included is coverage of the latest iPhone- and iPad-specific enterprise technologies (such as push notification and calendaring tools) as well as internal iPhone and iPad applications and web-based solutions for businesses.s
The Inevitability of the iPhone in the Enterprise -- Purchasing and Activating -- Applying Basic Configurations to Mobile Devices -- Integrating with Groupware -- Working with Documents and Files -- Remote Access for iOS -- Developing In-House Applications -- Building Configuration Profiles -- Mass-Deploying Devices -- Leveraging Third-Party Solutions for Productivity -- Developing A Program For Support.
Keywords: Computer science; Information systems; Computer Science; Computer Science, general; Information Systems and Communication Service